Perubahan Kadar N Tersedia Dan Populasi Azotobacter Di Rizosfer Sorgum (Sorghum bicolor L.) Yang Ditanam Di Dua Ordo Tanah Dengan Inokulasi Azotobacter sp. - Reginawanti Hindersah; D. A Sulaksana; D Herdiyantoro (Faculty of Agriculture, Pattimura University, 2014)
Bioagumentation by used of nonsimbiotic N2 fixing Azotobacter is a way to enhance soil N availability in sustainable Agricultural land. A green house experiment has been done to verify effect of Azotobacter sp. inoculation in two soil order, Inceptisols and Entisols, on NH4+danNO3- content , N uptake as well as Azotobacter population in rhizosphere soil of sorghum (Sorghum bicolor L.). Experiment was set up in Randomized Block Design with eight treatments and three replicates, sorghum was maintained in green house until maximum vegetative phase. Resuls showed that Azotobacter sp. AS4 was more enable to increase the availability of soil N rather than isolate AS3. Bacterial bioaugmentation with Azotobacter sp. AS4 on Inceptisols increased more NO3-, Azotobacter sp. population in soil rhizosphere and shoot height of sorghum genotype 2.24.